(3HfGA hEOGQI GdJMGdaGJ GdESJQGJjLjIs - (3LhQOGf O(B, (3dhjSs ((3GdbGgQI(B:s (3GdOGQ GdYQHjI ddfTQ(B,s, 1996)
(3EWGQ Yed GSJQGJjLj LOjO(B:(3deGPG CUHMJ GdJMGdaGJ ZGjI aj GdCgejI,GdJYGhf HgOa JMbjb ejRI JfGaSjI,GSJNOGe GdJMGdaGJ aj HfGA GdbOQI GdJShjbjI,CfhGY GdJMGdaGJ(B:(3GdYed eY GdJMGdaGJ ZjQ GdQSejI hGdJYGbOjI,GdJYGed eY GdJMGdaGJ PGJ GdGSJKeGQGJ GdUZjQI JfXje hEOGQI GdeTQhYGJ GdeTJQcI,GdJMGdaGJ eY GdLGeYGJ,GdJfajP(B:(3GdHMK GdODhH Yf GdaQU,GfJbGA GdTQcGA hHfGA GdJMGdaGJs
(3HHdjhZQGajG(B:(3U(B.5s
Keywords: (3EOGQI GdCYeGd GdYGeIs